The role of dopamine(2) receptor gene and personality characteristics in alcohol dependence in Turkish population - AKVARDAR, YILDIZ (CUMHURIYET UNIV TIP FAK PSIKIYATRI ANABILIM DALI, 2014)
Objective: Focusing on dopaminergic system, which is regarded to be responsible for alcohol dependence in many studies on animals and human beings, it is aimed to investigate Taql A and 8 allel polymorphisms of dopamine 2 receptor and personality characteristics in alcohol dependents and the relationship between these two parameters. Methods: In this study 64 alcohol dependent patients (3 females, 61 males) diagnosed according to DSM-IV diagnosis criteria, and 54 healthy subjects (8 females, 46 males) who themselves or whose first or second degree relatives had no alcohol dependence history were included. In order to determine their Taql A and 8 alleles, blood samples were drawn from the participants, and then they were applied Temperament and Character Inventory and Michigan Alcoholism Screening Test. Results: Subjects with and without alcohol dependence revealed no significant difference as regards the frequency of Taql A1 and B2 minor allel polymorphisms of DRD2 gene. It was also determined that the alcohol dependents had significantly higher scores in novelty seeking and harm avoidance dimensions, and lower scores in self directedness and cooperativeness dimensions than the controls. In alcohol dependents, no association was determined between the personality characteristics and Taql A1 and B2 minor allel polymorphisms. Conclusion: Not only one gene, but also several other minor genes in addition to personality characteristics and environment may play a role in vulnerability to alcohol dependence. In alcohol dependents, high novelty seeking is associated with the increase in impulsive behavior, and may be important for the onset of alcohol taking behavior. High level of harm avoidance may lead to taking alcohol continuously in order to deal with stress.
Keywords: Alcohol dependence; genetics; D-2 dopamine receptor gene (DRD2); Temperament and Character Inventory; personality; ALLELIC ASSOCIATION; NO ASSOCIATION; NOVELTY SEEKING; A1 ALLELE; D2; DRD2; POLYMORPHISMS; TRAITS; DRUG; D-2